2013
DOI: 10.1002/jsfa.6426
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope‐labelled feed nutrients to assess nutrient‐specific feed passage kinetics in ruminants

Abstract: Knowledge of digesta passage kinetics in ruminants is essential to predict nutrient supply to the animal in relation to optimal animal performance, environmental pollution and animal health. Fractional passage rates (FPR) of feed are widely used in modern feed evaluation systems and mechanistic rumen models, but data on nutrient-specific FPR are scarce. Such models generally rely on conventional external marker techniques, which do not always describe digesta passage kinetics in a satisfactory manner. Here the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In agreement with GS = grass silage (mainly ryegrass) with no inoculant; GS+S = grass silage with a short-term inoculant (applied 16 h before feeding); GS+L = grass silage with a long-term inoculant (applied at harvest); GS+S+L = grass silage with both long-and short-term inoculants. (Warner et al, 2014), retention times are well below the 72-h endpoint used with in vitro studies. The longer incubation time in vitro may explain the significant effects, but observed effects on digestibility in vivo are lacking.…”
Section: Dmi Diet Digestibility and Milk Yieldmentioning
confidence: 82%
“…In agreement with GS = grass silage (mainly ryegrass) with no inoculant; GS+S = grass silage with a short-term inoculant (applied 16 h before feeding); GS+L = grass silage with a long-term inoculant (applied at harvest); GS+S+L = grass silage with both long-and short-term inoculants. (Warner et al, 2014), retention times are well below the 72-h endpoint used with in vitro studies. The longer incubation time in vitro may explain the significant effects, but observed effects on digestibility in vivo are lacking.…”
Section: Dmi Diet Digestibility and Milk Yieldmentioning
confidence: 82%
“…Contrary to what is known about the monogastric, for which it has been clearly established that the small intestine is the main site of absorption for monomeric flavonoids, it is still unknown if flavonoids are absorbed across the rumen epithelium. However, several studies have shown an early peak in plasma flavonoid concentrations after intraruminal administration of quercetin [49] or consumption of a meal containing abundant isoflavones [50], thus suggesting that some flavonoids are adsorbed in the rumen, given that mean ruminal residence time of ingested feed is much greater than 1 h [51]. Consequently, flavonoids that come out of the rumen are probably absorbed in the small intestine due to the increase in the total plasma concentration of flavonol after intraduodenal infusion of quercetin [52].…”
Section: Bioavailability Of Polyphenols In Food-producing Animalsmentioning
confidence: 99%
“…Different substrates (soluble carbohydrates, starch, pectins, cellulose, hemicellulose and protein) that are fermented can be degraded at different rates also have a variable contribution to CH 4 production (Bannink et al, 2006). In cows, mean retention time of NDF components in the reticulorumen is around 28 h (using external markers, Schwarm et al, 2015) or 28-60 h (using intrinsic stable isotope labelling techniques, Warner et al, 2014), being longer than the standard in vitro incubation time of 24 h. Retention time in the reticulorumen is related to particle size (Schwarm et al, 2008). It can be argued that NDF fermentation during in vitro incubations probably approaches a plateau after 24 h given that relatively small feed particles (ca.…”
Section: Incubation Procedures and Ch 4 Measurementsmentioning
confidence: 99%